Logical Consistency in Controlling the Grammatical Rule - مرزوق بن عليّ فاتح (Milev Journal of Research and Studies, 2020)
This research deals with an important issue in the linguistic lesson in general, and the grammatical lesson in particular. As it addresses the issue of consistency in controlling the grammatical rule, even if in fact the matter is that consistency is a feature of the theoretical conditions of the linguistic phenomenon in general, and the grammatical phenomenon in particular; Because symmetry shows the true relevance of the grammatical lesson; Rather, it proves what the linguists and grammarians have prepared for the linguistic lesson, and especially if the matter is related to logicality in making grammatical rulings. Because in this case a lot has been said; It was related to Aristotelian grammar, and we will present a set of grammatical chapters to demonstrate this.